Features of small business management: current challenges in Ukraine - Davydenko, Oksana; Polovinkina, Ruslana; Biriukov, Tymur (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to a comprehensive analysis of the current state of state governance of Ukraine’s construction industry in the context of global economic transformations and the identification of key problems that hinder the effective functioning of this sector. The purpose of the study is to identify the main challenges in the system of state regulation of the construction sector and to develop practical recommendations for its improvement, taking into account modern technological and economic changes. The methodological basis of the research is built on the combination of systemic, comprehensive, and interdisciplinary approaches, which allows for an in-depth and well-reasoned analysis of the mechanisms of state governance of the construction industry under conditions of global economic transformation. The article provides a thorough analysis of the features of state governance of the construction sector of Ukraine in the context of digitalization and global economic changes. The main problems of state regulation of the construction industry are outlined, including: fragmentation of the legal and regulatory framework, lack of regulation of permit and approval procedures, absence of a unified national recovery policy, issues in urban planning, weak quality control in construction, shortage of qualified personnel in public administration, lack of transparent project monitoring, low level of digitalization in governance, the sector’s investment vulnerability, and insufficient consideration of environmental and social risks. Special attention is paid to the role of digital technologies in transforming the system of regulation of the construction industry. The article highlights the pathways for the digitalization of permit procedures, ensuring transparency and reducing corruption risks, and emphasizes the importance of cybersecurity and data protection. The practical aspect of the study lies in substantiating the need for comprehensive reforms in state governance of the construction sector, aimed at increasing the industry’s investment attractiveness and stimulating the introduction of innovations. JEL Classification: H70, М 13, O18, Q01, R51, R58